Effectiveness of arbuscular mycorrhizal fungi (AMF) and eco-enzyme on the growth of water spinach (Ipomoea aquatica) using a hydroponic system - Farmawaty Farmawaty; Gerardinalia Ngamelubun; Suharno Suharno; Puguh Sujarta; Irfaiz A. Ardiyansyah; Irjayanti irjayanti (Jurnal Biologi Papua, 2026)
The increasing generation of organic waste, particularly from household sources that are not properly managed, can have negative environmental impacts. One innovative solution is the utilization of waste for eco-enzyme production through fermentation, resulting in a liquid organic fertilizer product. On the other hand, arbuscular mycorrhizal fungi (AMF) are recognized as biological agents (biofertilizers) that can enhance plant nutrient uptake through mutualistic symbiosis with plant roots, thereby improving plant growth performance. This study aimed to evaluate the effectiveness of the combination of AMF and eco-enzyme on the growth of water spinach (Ipomoea aquatica) using a hydroponic system. The study employed a completely randomized design (CRD) with several treatments, namely: (1) control (without fertilizer), (2) positive control (AB-Mix chemical fertilizer), (3) eco-enzyme (liquid organic fertilizer), and (4) a combination of AMF + eco-enzyme, each with three replications. The results showed that eco-enzyme application did not have a significant effect. Although the addition of AMF and eco-enzyme resulted in plant height, leaf number, leaf area, root length, fresh weight, and dry weight, these responses were not superior to the control. Although the percentage of AMF colonies was high in I. aquatica, the use of AB-Mix fertilizer, either alone or in combination with AMF, still performed better than eco-enzyme.